The personality of the Palestinian prisoner according to the theory of the five major factors and their relationship to some variables - Abu Shaban, Shaima Sobhi; Al-Yazji, Ibtisam Rashid (Journal of Educational and Psychological Sciences, 2020)
The research aims to uncover the distinguishing factors of the Palestinian prisoner’s personality according to the theory of the five major factors. The research was based on a sample of 60 prisoners who were liberated in the free deal. The research was based on descriptive approach., Edited by: Costa and Macri: Arabic Translation Badr Al-Ansari 1997, in order to reveal the most prominent factors in the personality of the prisoner liberated and the effect of variable (duration of detention- and the age) on those factors. The results of the research were as follows: The factor of the good was ranked first with a high relative weight followed by wakefulness of the conscience and then the neurotic and then Alastasatip and then Safwa where the Safwa in the last mattress and the least relative weight in the statistical analysis, There are no statistically significant differences in the response of the sample of the Palestinian prisoners on the effect of the age of the prisoner on the five major factors of the personality, There were no statistically significant differences in the response of the sample of the Palestinian prisoners on the effect of the detention period on the five major factors of the personality, In light of these results, the researchers recommended that: Conducting numerous studies on Palestinian prisoners that serve their cause. , and not to ignore the needs of prisoners material and moral and the need for follow-up by specialists in the matter, Holding several training programs that serve the prisoners and help them in positive adjustment with the community.